The Andalusian Public Remembrance in Aragon, a Premeditated Oblivion? - Adiego Sevilla, Ramiro (Historiografías, 2025)
The Islamic past in Spain has always been a problematic object. However, in the current context of the rise of the extreme-right movements, the political use of Spain’s medieval history has reached new proportions. We shall analyze this situation in the specific case of Aragon to discuss how its institutions have ignored the Andalusian public memory. We defend that this omission has transferred a distorted image of the past which is fed of racist and nationalist discourses from the present. Keywords Al-Ándalus, historical revisionism, Reconquista, historiography, Saraqusta, extreme right.